The effect of cognitive behavioural therapy on pain and disability in chronic non-specific low back pain: An overview of systematic reviews - Tiffany Leung; Mei Ken Low; Pei Chi Yao; Ana-Catarina Pinho-Gomes (PLoS ONE, 2025)
Background Low back pain (LBP) is experienced by most people at least once in their lifetime and is the leading cause of disability worldwide. Cognitive behavioural therapy (CBT) is a non-invasive method used to manage chronic non-specific low back pain (CNSLBP) and contains less adverse effects than analgesic medications. Aims To determine the efficacy of interventions incorporating CBT on reducing pain intensity and physical disability in CNSLBP. Methods An overview of reviews without meta-analysis was conducted. Four electronic databases (MEDLINE, Embase, Cochrane Library and PsycINFO) were searched. Adults aged 18 or above with CNSLBP were included. AMSTAR 2 was used to assess risk of bias of included systematic reviews and data synthesis was conducted via vote counting methods. Results Ten systematic reviews were included. Results showed that CBT is more effective in reducing pain and disability compared to waiting list/usual care (WL/UC). CBT in conjunction with other active treatments (AT) are also more effective than some standalone AT such as physiotherapy and exercise, but less effective than surgery. Conclusion CBT has some effect in reducing pain and disability, however, it may not be more effective than other treatments. The quality of evidence was low for most outcomes as there was high risk of bias and heterogeneity between studies. Future research could evaluate specific therapies such as acceptance and commitment therapy (ACT) and mindfulness-based cognitive therapy (MBCT), as these treatments lacked primary studies. There is no recognised standard for conducting CBT, and further research could determine the most effective duration, mode of delivery (e.g., online, group-based) and intensity of CBT.